A portrait of affective assessment implementation in junior high schools: Assessing its ideality - Charismana, Dian Satria; Ratri, Safitri Yosita; Firmansyah, Firmansyah (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Ideal assessment in teaching and learning should involve the cognitive, affective, and psychomotor domains following the Merdeka Belajar curriculum, which emphasizes Pancasila values. However, whether teachers can develop affective domain assessments optimally is still questionable. A literature study has been conducted by researchers and found that in Indonesia, teachers tend to develop cognitive domain assessments more than affective and psychomotor domain assessments. Therefore, this research uses a phenomenological approach to investigate the implementation of affective domain assessment conducted by school teachers. The participants of this study consisted of 18 middle school teachers in Indonesia. Data were collected through open-ended questionnaires, interviews, and focus group discussions (FGDs). Data analysis was conducted using the model by Miles, Huberman, and Saldana, which consists of three stages: 1) data reduction, 2) data display, and 3) conclusion drawing. The study found that teachers understand affective assessment well and emphasize the importance of instilling affective values in education to reduce moral problems. They also emphasize the need for changing teaching strategies and providing relevant materials to help students understand their lessons. However, the planning for affective assessment is time-consuming and the implementation in middle schools is not ideal. Subject teachers often handle this assessment, which should be the responsibility of all teachers, rather than just Religion, Guidance and Counseling, and Civic Education.